Phytochemical Study and Antibacterial Activity of Ethanolic Extracts of Azadirachta indica Leaves on Previously Profiled Multidrug Resistant Aerobic Bacteria (African Journal of Biomedical Research, 2023)
The challenge of antimicrobial resistance of pathogenic microbes, continues to be a global issue and sourcing of new antimicrobial compounds is still more challenging. The study of active plant components can be a lead to aid in the discovery of new efficacious antimicrobial agents. Azadirachta indica, known as Neem, is used in Phytotherapy and Herbal medicine. It possesses an array of biologically active compounds having anti-inflammatory, antimalarial, antifungal, antibacterial, antiviral properties amongst other therapeutic activities. This study is aimed at the qualitative and quantitative determination of the phytochemical constituents and the extent of inhibition by the ethanolic extract of Neem leaves on selected Gram positives organisms; all known to be Methicillin resistant Staphylococcus aureus (MRSA), from a previous study and Gram-negative organisms, which are known to be multidrug resistant  (MDR) also from a previous study. The presence of alkaloids, saponins,phenolics, flavonoids,tannins,cardiac glycosides, steroids were detected. Cardiac glycosides quantity was highest (1.569mg/g) followed by alkaloids (0.42mg/g) and saponins (0.32mg/g).Others were below 0.1mg/g. A.indica ethanolic leaf extract exhibited antibacterial activity on only one strain of Klebsiella pneumonia, Med 1(2) with the maximum zone of inhibition (25 mm) obtained at 400mg/ml and MIC value of 160 mg/ml. All the Staphylococcus species except Med. 4k, gave varying zones of inhibition (14mm – 34mm) over the range of concentrations (400mg/ml to 100mg/ml) used for the test and MIC values (5.12 mg/ml to 40 mg/ml). This study indicates that the ethanolic leaf extracts of Azadirachta indica have good potentials as Antimicrobials against infections of MRSAs.
Keywords: Azadirachta indica; Neem leaves; Phytochemical; Multi-drug resistant; Herbal medicine; Anti-microbials